2015
DOI: 10.1017/jfm.2015.132
|View full text |Cite
|
Sign up to set email alerts
|

Rogue waves in opposing currents: an experimental study on deterministic and stochastic wave trains

Abstract: Rogue waves in opposing currents: An experimental study on deterministic and stochastic wave trains / Toffoli, A; Waseda, T.; Houtani, H.; Cavaleri, L.; Greaves, D.; Onorato, M

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…1). Data were recorded at a sampling frequency is 100 Hz (the set up for this experiment is described in details in [25,26]).…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…1). Data were recorded at a sampling frequency is 100 Hz (the set up for this experiment is described in details in [25,26]).…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…From this perspective of anomalous behavior, rogue waves can be considered under the more general framework of turbulent dynamical systems [17,23,25,24,7,16]. Several physical mechanisms have been shown to produce rogue waves, most notably the Benjamin-Feir (BF) instability that occurs in deep water 1 [2,20,6,32,1,8,5,10], as well as wind excitation [3,28], opposing currents [21,29], and geometric ray focusing from 2D bathymetry [13,33].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of a background current on the resonance has been studied for the degenerate case of modulational instability of a Stokes wave, which plays a pivotal role in freak wave generation, by Toffoli et al (2013Toffoli et al ( , 2015. They have experimentally confirmed the foresight of Onorato, Proment & Toffoli (2011), who have shown that the generation of rogue waves is triggered when waves enter a field of opposing current.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, the flow makes an abrupt 90 • turn behind the guide walls under the wavemaker and beneath the beach. Because of this configuration, the mean current field is not uniform across the tank and has a vertical shear as well (figure 1 and also Toffoli et al 2013Toffoli et al , 2015. The coflowing current is better regulated than the opposite condition because of the different inlet and outlet configurations.…”
Section: Facility and Experimental Conditionsmentioning
confidence: 99%